COMPARATIVE STUDY OF INTRACYTOPLASMIC SPERM INJECTION OUTCOME FROM SPERMS RETRIEVED BY DIFFERENT PROCEDURES - Ali, Shazia; Ashraf, Nasim; Siddique, Anjum Ara; Jalali, Samina; Shami, Sajjad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Different sperm retrieval procedures can help retrieve sperms that can be used for Intracytoplasmic Sperm Injection (ICSI) in azoospermic men. The objective was to compare the Intracytoplasmic sperm injection outcome, through different sperm retrieval procedures in azoospermic men. Methods: A Retrospective Study was carried out at Islamabad Clinic Serving Infertile Couples from September 1999 to March 2005. The study includes 105 female subjects and 105 male azoospermic subjects. In 105 male subjects 50 subjects had Non-Obstructive Azoospermia (NOA) and 55 subjects had Obstructive azoospermia (OA). These subjects underwent surgical sperm retrieval procedures like Percutaneous Epididymal Sperm Aspiration (PESA) or Fine Needle Aspiration Biopsy. Intracytoplasmic sperm injection (ICSI) was performed from both and outcome was compared. All the values were expressed as Mean±SE. Limit of significance was set at (p<0.05). Mean values were compared using unpaired Students t-test. Results: Subjects who underwent ICSI procedure with motile sperms retrieved through Biopsy had significantly (p<0.05) raised cleavage rate and live birth rate. Conclusion: No matter what ever the procedure of sperm retrieval used, the sperm motility has great significance. Significantly raised live birth rate was detected in subjects where sperms retrieved through biopsy were used for ICSI procedure. Keywords: Intracytoplasmic Sperm Injection (ICSI), Percutaneous epididymal sperm aspirate (PESA), testicular biopsy, azoospermia, infertility